2013
DOI: 10.1080/03056244.2013.794725
|View full text |Cite
|
Sign up to set email alerts
|

Industrial policy and the political settlement in Tanzania: aspects of continuity and change since independence

Abstract: This article explores Tanzania's experience of industrial policy since independence through the concept of the political settlement. Higher growth in manufacturing since 1996 has been seen as a vindication of neoliberal policies of market liberalisation. Yet, the neoliberal approach fails to take account of the important legacy of state-led industrialisation under socialism and aspects of the political economy of the state in Tanzania that explain some of the longer-term constraints on industrialisation. Criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…This has brought about a growing number of formal channels for SBRs, though informal channels continue to play a significant role. This transition heralded the development of more open relationship between the state and private enterprises accompanied with the formal institutions linking the private sector and the state (Gray, 2013). The current policy framework puts emphasis on promoting and empowering the private sector to take the lead in growing the economy (Charles, 2014).…”
Section: Sbrs In Kenya Tanzania and Zambia In A Historical Contextmentioning
confidence: 99%
“…This has brought about a growing number of formal channels for SBRs, though informal channels continue to play a significant role. This transition heralded the development of more open relationship between the state and private enterprises accompanied with the formal institutions linking the private sector and the state (Gray, 2013). The current policy framework puts emphasis on promoting and empowering the private sector to take the lead in growing the economy (Charles, 2014).…”
Section: Sbrs In Kenya Tanzania and Zambia In A Historical Contextmentioning
confidence: 99%
“…Quite simply, African leaders have rarely found it in their interests to promote broad-based development. Without state frameworks for growth, foreign investment has flown into extractive enclaves and export sectors where private forms of security and governance frameworks secure investment (Reno, 1999;Hibou, 2004;Ferugson, 2005;Abbink, 2011 Gray andKhan, 2010 andGray, 2013 on Tanzania). He and his colleagues have shown that while private companies received privileged treatment that gave them unfair advantages, they were only permitted to do so when they contributed to broader developmental objectives.…”
Section: State Power and Economic Development: Motivation Mattersmentioning
confidence: 99%
“…In Africa, textile production has a long history prior to and during colonial rule. Many newly independent African governments invested heavily in the sector as part of 'import substitution industrialization' (ISI) strategies (Mkandawire & Soludo, 1998;Gray, 2013). By the late 1960s, Uganda was the largest cotton producer in sub-Saharan Africa (Baffes, 2009).…”
Section: Protecting East African Textilesmentioning
confidence: 99%